2007
DOI: 10.1089/aid.2007.0054
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication:Comparative Longitudinal Studies of HERV-K and HIV-1 RNA Titers in HIV-1-Infected Patients Receiving Successful versus Unsuccessful Highly Active Antiretroviral Therapy

Abstract: The viral kinetics of HERV-K in HIV-1-infected patients receiving highly active antiretroviral therapy (HAART) is not unknown. HERV-K kinetic modeling may provide insight into factors altering the effectiveness of HAART in suppressing HIV-1 burden. We conducted a longitudinal study measuring the HERV-K RNA titers in four patients with successful HIV-1-suppressive HAART and in six patients undergoing HAART failure. HERV-K titers were usually undetectable in patients with successful HAART, and when detected, HER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 16 publications
1
48
1
Order By: Relevance
“…APOBEC deaminases have been shown to inhibit infection with HK2 viruses (52, 91); therefore, the expression of HIV-1 Vif may counteract this effect. These findings are consistent with those from our group and others, who have found increased expression of HK2 viruses in the setting of HIV-1 infection (9,10,(24)(25)(26)(27)92). The consequence of this increased expression of transmissible HK2 viruses, for both HIV-1-infected cells and the HIV-1-infected individual, remains to be elucidated.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…APOBEC deaminases have been shown to inhibit infection with HK2 viruses (52, 91); therefore, the expression of HIV-1 Vif may counteract this effect. These findings are consistent with those from our group and others, who have found increased expression of HK2 viruses in the setting of HIV-1 infection (9,10,(24)(25)(26)(27)92). The consequence of this increased expression of transmissible HK2 viruses, for both HIV-1-infected cells and the HIV-1-infected individual, remains to be elucidated.…”
Section: Discussionsupporting
confidence: 92%
“…We next asked whether expression of HIV-1 viral proteins increases the production of transmissible HK2 VLPs. The rationale behind this approach is that HIV infection, specifically the expression of the HIV-1 Tat and Vif proteins, has been found in previous studies to enhance expression of HK2 (9,10,24,26,27,85,86). Expression of HIV-1 Tat and Vif, but not Vpu, in NCCIT cells increased the production of transmissible HK2 VLPs containing the Bogota probe, as determined by measuring the number of G418-resistant clones (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, external stimuli, such as infections, viral transactivators, chemical exposures, cytokines, hormones, and inflammation, can induce expression of these proviruses (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). We and others have shown that HIV-1 infection is associated with increased HERV-K (HML-2) expression in vitro and in vivo (33,(45)(46)(47)(48)(49)(50)(51)(52)(53). Compared to healthy individuals, HIV-1-infected individuals show high levels of HERV-K (HML-2) RNA, DNA, protein, and viral particles in their plasma (45,47,48,50).…”
mentioning
confidence: 99%
“…We and others have shown that HIV-1 infection is associated with increased HERV-K (HML-2) expression in vitro and in vivo (33,(45)(46)(47)(48)(49)(50)(51)(52)(53). Compared to healthy individuals, HIV-1-infected individuals show high levels of HERV-K (HML-2) RNA, DNA, protein, and viral particles in their plasma (45,47,48,50). This HIV-1-mediated activation of HERV-K (HML-2) is partially due to the HIV-1 Tat protein activating the NF-B and NF-AT transcription factors, which then interact with the HERV-K (HML-2) LTR promoter to stimulate transcription (46).…”
mentioning
confidence: 99%